Not As Good as You Think? Trait Positive Emotion Is Associated with Increased Self-Reported Empathy but Decreased Empathic Performance - Devlin, Hillary C.; Zaki, Jamil; Ong, Desmond C.; Gruber, June (PLOS ONE, 2014)
How is positive emotion associated with our ability to empathize with others? Extant research provides support for two competing predictions about this question. An empathy amplification hypothesis suggests positive emotion would be associated with greater empathy, as it often enhances other prosocial processes. A contrasting empathy attenuation hypothesis suggests positive emotion would be associated with lower empathy, because positive emotion promotes self-focused or antisocial behaviors. The present investigation tested these competing perspectives by examining associations between dispositional positive emotion and both subjective (i.e., self-report) and objective (i.e., task performance) measures of empathy. Findings revealed that although trait positive emotion was associated with increased subjective beliefs about empathic tendencies, it was associated with both increases and decreases in task-based empathic performance depending on the target’s emotional state. More specifically, trait positive emotion was linked to lower overall empathic accuracy toward a high-intensity negative target, but also a higher sensitivity to emotion upshifts (i.e., shifts in emotion from negative to positive) toward positive targets. This suggests that trait positive affect may be associated with decreased objective empathy in the context of mood incongruent (i.e., negative) emotional stimuli, but may increase some aspects of empathic performance in the context of mood congruent (i.e., positive) stimuli. Taken together, these findings suggest that trait positive emotion engenders a compelling subjective-objective gap regarding its association with empathy, in being related to a heightened perception of empathic tendencies, despite being linked to mixed abilities in regards to empathic performance. (Word count: 242).